Fluid-Structure Interaction Analysis of a Cropped Delta Wing. (2016) - Kumar, A. Arun; Manoj, N.; Onkar, Amit Kumar; Manjuprasad, M.
Abstract: The fluid-structure interaction behaviour of a cropped delta wing is investigated using a computational fluid dynamics (CFD) based aeroelastic solver in time domain. Here, an N-S based finite volume solver is coupled with a finite element based linear and nonlinear structural solvers to study the nonlinear aeroelastic characteristics of the delta wing over a range of dynamic pressures. The amplitude and frequency obtained from the present coupled solver at various dynamic pressures are compared with the available experimental and computational results.